Upaya Meningkatkan Produksi dan Kualitas Buah Jambu Biji Kristal (Psidium guajava L. cv. Kristal) Melalui Pemupukan - MAHENDRA, I GEDE JAYA; RAI, I NYOMAN; WIRAATMAJA, I WAYAN (Agrotrop : Journal on Agriculture Science, 2017)
Efforts to Increase Production and Quality of “Kristal” Guava Variety (Psidium guajava L. cv. Kristal) by Fertilization. Nowadays “Kristal” guava variety (Psidium Guajava L. cv. Kristal) is very popular for consumers because it has several advantages such as flesh fruit is crunchy, sweet-sour taste with slightly seeds or seedless, and shelf life of fruit relatively long that can be up to 1 month if stored at temperature of 10-15 oC. The challenge faced by farmers are the production and fruit quality still low, due to inadequate maintenance done. This research was conducted to study the effect of fertilizer to increase the production and quality of “Kristal” guava variety. Research was carried out in farmers garden at Pelaga Village, District of Petang, Badung Regency, Bali, from April-November 2016. The study was a randomized block design (RBD) with fertilizer treatment consisted of 4 levels and each repeated 6 times. The results showed that fertilization increase production and quality of “Kristal” guava fruit compared to the control. The highest weight of fruit per plant (18.28 kg / plant) were obtained on plants fertilized with compost 5kg/plant + urea 200 g/plant + KCl 250 g/plant + TSP 250 g/plant + gypsum 500 g/plant+ micro fertilizer CuSO4 and ZnSO4 1.5 g/plant, respectively, given once at the beginning of the study and significantly different compared to the lowest weight of fruit per plant which obtained on controls (8.99 kg/plant). The highest fruit diameter (8.72 cm) obtained on plants fertilized with compost 5kg/plant + urea 200 g/plant + KCl 250 g /plant + TSP 250 g / plant + gypsum 500 g/plant + micro fertilizer CuSO4 and ZnSO4 each 1.5 g/plant, respectively, given three times i.e at the beginning of the study, at the phase of anthesis, and at the maturity of fruit and significantly different compared to control (7,50 cm).